Acute cardiotoxic effects of high dose toluene: an experimental study - Tas, Ufuk; Ekici, Fatih; Koc, Fatih; Sogut, Erkan; Ayan, Murat; Kuloglu, Tuncay; Ozyurt, Birsen (Kare Publ, 2013)
Objective: This study aimed to investigate the acute cardiotoxic effects of high dose toluene and its damage mechanisms on heart tissue in the acute period. Methods: Twenty adult male Wistar Albino rats (200-220 g) were used in this controlled experimental animal study. Animals were divided into two equal groups: a control group (Group 1) and a high dose (6 mL/kg/gavage) toluene-administered group (Group 2). Arterial blood pressure (BP) and heart rate (HR) values were measured at 30th, 60th and 90th minutes after toluene was administered. At the end of the experimental period, blood samples and heart tissues were taken from the rats. Serum troponin T levels were assayed. Heart tissue sections were stained using routine histological methods and examined under a light microscope. In addition, the sections were immunohistochemically stained using the avidin-biotin-peroxidase method to determine caspase-3 immunoreactivity and TUNEL to detect apoptosis. To compare the apoptotic index, the Mann-Whitney U test was used. For comparisons between the two groups, the independent t- test was used. In addition, time-based changes of intra-group parameters were evaluated using paired t tests. Results: BP and HR values were low in toluene-treated rats compared to the control group. Troponin T levels were increased in toluene-administered animals as compared with controls [Toluene group: 0.140 (0.010-2.000) ng/mL vs control group: 0.010 (0.010-0.010) ng/mL, p=0.01]. Histopathologic examination of heart tissue sections showed congestion and edema in toluene administrated rats. Higher TUNEL positivity and (+++) immunoreactivity for caspase-3 protein were observed in the toluene group compared to the control group. Conclusion: The present study demonstrated that high doses of toluene cause apoptosis and may lead to impairment of cardiac function in the acute period. (Anadolu Kardiyol Derg 2013; 13: 3-8)
Yüksek doz tolüenin akut dönemdeki kardiyotoksik etkisi: Deneysel bir çalışma
Keywords: Toluene; cardiovascular toxicity; immunohistochemistry; apoptosis; troponin T